Purification, crystallization and preliminary X-ray crystallographic analysis of ST1022, a putative member of the Lrp/AsnC family of transcriptional regulators isolated from Sulfolobus tokodaii strain 7 - Nakano, Noboru (International Union of Crystallography, 2007)
The Lrp/AsnC family of transcriptional regulators, also known as feast/famine transcriptional regulators, are widely distributed among bacteria and archaea. This family of proteins are likely to be involved in cellular metabolism, with exogenous amino acids functioning as effectors. Here, the crystallization and preliminary X-ray diffraction analysis of ST1022, a member of the Lrp/AsnC family of proteins, is reported with and without exogenous glutamine as the effector molecule. The crystals of native ST1022 and of the putative complex belong to the tetragonal space group I422, with unit-cell parameters a = b = 103.771, c = 73.297 Å and a = b = 103.846, c = 73.992 Å, respectively. Preliminary X-ray diffraction data analysis and molecular-replacement solution revealed the presence of one monomer per asymmetric unit.